Single Injection of Cross-Linked Hyaluronate in Knee Osteoarthritis: A 52-Week Double-Blind Randomized Controlled Trial - Po-Yen Ko; Chung-Yi Li; Chia-Lung Li; Li-Chieh Kuo; Wei-Ren Su; I-Ming Jou; Po-Ting Wu (MDPI AG, 2022)
Background: to compare the 52-week effectiveness and safety between HYAJOINT Plus (HJP) and Durolane in knee osteoarthritis (OA) treatment. Methods: consecutive patients received a single injection of 3 mL HJP or Durolane. The primary outcome was a visual analog scale (VAS) pain measurement at 26 weeks post-injection. Secondary outcomes included other clinical, satisfaction, and safety assessments for 52 weeks. Results: 142 patients were equally randomized. At week 26, the HJP group had less VAS pain than the Durolane group (18.1 ± 9.5 versus 24.4 ± 14.0, p = 0.001). Both groups showed improvement in their VAS pain and stiffness scores, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain and total scores for 52 weeks after injection (p < 0.001). However, the HJP group showed lower VAS pain and stiffness scores, reduced WOMAC pain and stiffness scores, a shorter Timed "Up & Go" (TUG) time, and a higher satisfaction score than the Durolane group for 39 weeks (p < 0.05). Only mild and self-limited adverse events occurred (40.8%). Conclusion: While a single injection of either HJP or Durolane is safe and effective for at least 52 weeks, HJP provided superior improvement in terms of VAS pain and stiffness scores, WOMAC pain and stiffness scores, and satisfaction score within 39 weeks of treatment.